Correlations and Weights in the Admission Exams-UNI - Ordóñez Mercado, Alipio Francisco (2005)
The selection of the best students in the admission process is a complex and delicate task. In this paper, a new weighting is proposed to obtain the general admission score, using the multivariate technique of "Factor Analysis". The results found reveal three important components: Scientific Support, with 56%, General Culture, with 29% and Skills and Skills with 15%. This weighting preserves a high concordance with the traditional form, since there is a modification in the orders of merit of only 12% of the cases.